Lembar Kerja Laboratorium Berbasis Proyek Pembuatan Koloid dengan Pemanfaatan Daun Cincau Perdu (Premna Oblongifolia) - Siti marfu'ah; Annisa Meristin (Chemistry Education Department of Education and Teaching Faculty, 2022)
Chemistry practicum is still only concept verification or is a cookbook.This study aims to develop student worksheets on producing jelly as a colloid product by using perdu cincau leaves (Premna Oblongifolia). The method used in this study is development research with ADDIE models (Analysis, Design, Development, Implementation, Evaluation), which only done until development step. Analysis curricula of colloid topic and study of literature on project-based practicum and perdu cincau leaves have been carried out at analysis step. At this step also interviewed high school teachers and found that there is no student worksheets for supporting KD 4.15. At design step, the experiment of jelly producing using perdu cincau leaves was optimized and the best laboratory work design was obtained, such as materials, tools and procedures. Then, a project-based laboratory worksheet draft was created and validated by experts. Based on the suggestions given by the validator, content number 11 was omitted because it contained irrelevant instructions. Content number 2 added instructions. Content number 15 and 16 an explanation is added. Content number 3, 4 and 12, it is necessary to edit sentences. After revising, student worksheets is ready to be implemented in learning activities.